Experiences in Youth Sports: A Comparison Between Players’ and Parents’ Perspectives - Keri A. Schwab; Mary Sara Wells; Skye Arthur-Banning (Journal of Applied Sports Management, 2010)
A key difficulty for administrators of youth sport programs is satisfying both parents (as those who make the final decision of participation) and players (as those for whom the program is designed). While both stakeholders have important viewpoints, the potential exists for stark differences between the two. This paper explores the differences between players’ and parents’ perspectives of a youth sport experience. Results suggest that players generally tend to think more positively than parents of the youth sport program, including areas such as skill development, teamwork development, character development, sportsmanship, and fun. Suggestions for practitioners on how to address these issues are included.
Keywords: Youth Sport; Perspectives; Parents; character development; teamwork; sportsmanship; play; recreation administration